2000
DOI: 10.1051/rnd:2000137
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that growth factors IGF-I, IGF-II and EGF can stimulate nuclear maturation of porcine oocytes via intracellular protein kinase A

Abstract: -The aim of our in vitro experiments was to study the role of growth factors and protein kinase A (PKA)-dependent intracellular mechanisms in the control of nuclear maturation of porcine oocytes. Oocytes were cultured with or without growth factors (IGF-I, IGF-II, EGF; 10 ng . mL -1 medium) and inhibitors of PKA (Rp-cAMPS or KT5720; 100 ng . mL -1 ). Stages of meiosis were determined from the structure of chromosomes after staining with Giemza. Intracellular levels of PKA were evaluated immunocytochemically us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 38 publications
6
42
2
3
Order By: Relevance
“…Requirement of MAPK/ ERK1-2 for promotion of meiosis is confirmed by the inhibitory effect of MAPK blocker PD98059 on both MAPK/ERK1-2 accumulation and oocyte maturation after culture observed in our experiments. Our observations are in line with maturationassociated accumulation or activation of MAPK and with the ability of MAPK blocker to prevent meiosis in porcine oocytes observed by other authors (Inoue et al, 1995 andMotlik et al, 1998;Lee et al, 2000;Sirotkin et al, 2000;Wehrend and Meinecke, 2001;Ye et al, 2007;Ebeling et al, 2007; …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Requirement of MAPK/ ERK1-2 for promotion of meiosis is confirmed by the inhibitory effect of MAPK blocker PD98059 on both MAPK/ERK1-2 accumulation and oocyte maturation after culture observed in our experiments. Our observations are in line with maturationassociated accumulation or activation of MAPK and with the ability of MAPK blocker to prevent meiosis in porcine oocytes observed by other authors (Inoue et al, 1995 andMotlik et al, 1998;Lee et al, 2000;Sirotkin et al, 2000;Wehrend and Meinecke, 2001;Ye et al, 2007;Ebeling et al, 2007; …”
Section: Discussionsupporting
confidence: 93%
“…The nuclear maturation of porcine oocytes after isolation and culture, as well as the presence of MAPK/ERK1-2 in these oocytes, is in line with previous reports (Inoue et al, 1995 andMotlik et al, 1998;Lee et al, 2000;Sirotkin et al, 2000;Wehrend and Meinecke, 2001;Ye et al, 2007;Ebeling et al, 2007;Kimura et al, 2007;Li et al, 2008). It was shown that a part of the oocytes were mature already before long-term culture.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, it has been established that IGF-1 has a beneficial effect on oocyte nuclear maturation [21,22], whereas, oocyte expresses IGF-1 receptor [23]. Forthermore, IGF-1 stimulates resumption of meiosis and completion of nuclear maturation of porcine oocytes [24]. It has been detected that exposure of bovine oocytes to EGF and IGF-1 accelerated progression of meiosis in COCs [25].…”
Section: Discussionmentioning
confidence: 99%